2023
DOI: 10.3390/su15032840
|View full text |Cite
|
Sign up to set email alerts
|

Can Digital Transformation Drive Green Transformation in Manufacturing Companies?—Based on Socio-Technical Systems Theory Perspective

Abstract: The current world’s green economy and digital economy collide at an accelerated pace, and the deep integration of digitalization and greening has become a new requirement for high-quality industrial transformation. Premised on a socio-technical system (STS)’s theoretical viewpoint from Chinese manufacturing firms, the study examines the effects of the digital transformation (DT) of companies on green transformation (GT), as well as the function of channels and processes. This study uses 70 samples of A-share-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…This study indicates that DT facilitates the process of GT in enterprises. This finding is in line with Zhang [9] and Waqas [124]. Digital transformation brings productivity and organizational performance improvements to companies, making it an inevitable choice for the future development of Chinese companies [14].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This study indicates that DT facilitates the process of GT in enterprises. This finding is in line with Zhang [9] and Waqas [124]. Digital transformation brings productivity and organizational performance improvements to companies, making it an inevitable choice for the future development of Chinese companies [14].…”
Section: Discussionsupporting
confidence: 72%
“…Digitalization on the production side brings new changes in production processes, decision making, and environmental monitoring to enterprises and becomes the basis for GT [78,79]. At the same time, digitalization on the service side enables enterprises to provide targeted advice and services to customers and move towards intelligence, proactivity, and personalization, helping enterprises to achieve their GT through demand-sidedriven green development [9]. Based on this, the behavioral attitude that digitalization drives GT, represented by ATT, is measured from the production side and the service side in 2 dimensions, and 5 question items are set, which are represented by ATT1, ATT2, ATT3, ATT4, and ATT5, respectively.…”
Section: Attitude (Digitalization Drives Gt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Little of the published work on green and digital transition has looked to provide a theoretical framework to help to guide and structure future research or to help to locate it within business and/or social structures, but Zhang et al (2023) used the perspective of socio-technical systems theory to examine the green empowerment of digital technology, in relation to manufacturing industry in China. More generally, Zhang et al (2023) suggested that technical systems theory suggested that managers can play an important role in the interaction between technological and social systems, and this has implications for the role of tourism managers in developing green and digital transition policies.…”
Section: Literature Searchmentioning
confidence: 99%
“…The 14th Five‐Year Industrial Green Development Plan points out that digital transformation drives the change of production methods, enhances resource and ecological management by adopting digital technology, and empowers green manufacturing 4 . De depends on technical supremacy to accelerate the greening of industrial production mode under real‐time analysis, state awareness, and precise execution of energy management systems (Zhang, Nutakor, et al, 2023; Zhang, Xu, & Aoki, 2023; Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%